Utilization of electronic marketing and economic determinants to improve income of dairy cattle farmer in Boyolali, Central Java - Indonesia - Setiadi, A.; Santoso, S. I.; Mukson, M.; Nurfadillah, S.; Prayoga, K. (Diponegoro University, 2020)
This study aimed to analyze the impact of electronic marketing utilization and to determine the economic determinants to increase the income of small dairy farmers in Boyolali, Central Java, Indonesia. A survey of 80 dairy farmers from the Cepogo District, Boyolali was determined by simple random sampling. The results showed that the average milk production was 8.3 liters/head/day, the revenue of IDR 3,824,000 per month, production costs of IDR 2,105,000 per month, and income of IDR 1,719,000 per month. Furthermore, by using electronics marketing, farmers could sell 40% of their products to coffee shops and generate revenue of IDR 5,411,500, production costs of IDR 2,705,000 and income of IDR 2,706,500. The utilization of the electronic marketing could increase R/C from 2.1 to 2.43. Economic factors that influence income are market prices, transportation and communication costs, marketing costs and distance traveled. Based on the results of the study it can be concluded that the use of the electronic market can expand the market, increase milk prices and ultimately will increase income